The Impact of Hepatitis B Virus Precore/Core Gene Carboxyl Terminal Mutations on Viral Biosynthesis and the Host Immune Response - Wu, Jia-Feng; Ni, Yen-Hsuan; Chen, Huey-Ling; Hsu, Hong-Yuan; Chang, Mei-Hwei (The Journal of infectious diseases, 2014)
Background. We aimed to elucidate the impact of hepatitis B virus (HBV) precore/core gene mutations on spontaneous hepatitis Be antigen (HBeAg) seroconversion, HBV biosynthesis, and the human immune responses in chronic HBV–infected patients. Methods. We analyzed the HBV precore/core gene sequences by cloning method in 33 chronic HBV–infected patients during the inflammatory phase before spontaneous HBeAg seroconversion. The impact of the most prevalent mutant on HBeAg biosynthesis was assessed by Western blotting and native agarose gel analysis in Huh7 cells, and the human immune responses were assessed by in vitro stimulation of CD3⁺ CD8⁺ T lymphocytes of chronic HBV–infected subjects. Results. The P135Q and G1896A were the most prevalent mutants before HBeAg seroconversion, acting as markers of HBeAg seroconversion (hazard ratios = 2.75 and 4.50; P=.01 and <.001, respectively). The P135Q mutants displayed decreased HBeAg secretion and HBV capsid molecular weight, while showing increased 22 kD HBeAg proprotein accumulation in Huh7 cells. The P135Q mutant peptide induced less interferon-γ expression in CD3⁺ CD8⁺ T lymphocytes in HBeAg-negative subjects compared to the wild-type peptide (P = .03). Conclusions. The HBV P135Q mutant emergence during the inflammatory phase was associated with HBeAg seroconversion. It was associated with altered HBV capsid assembly, HBeAg biosynthesis, and reduced human immune responses following HBeAg seroconversion.